The Relationship Between Parental Attention and Learning Outcomes of Darul Izzah Abai Rumah Tahfidz Qur'an (RTQ) Students, South Solok - Frengki Candra Kusuma; Vevi Sunarti (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research is suspected by the low learning outcomes of RTQ Darul Izzah Abai Solok Selatan students. This research aims to see: (1) a description of parents' attention to the Darul Izzah Abai South Solok Tahfidz Qur'an (RTQ) house, (2) a picture of the learning outcomes of students at the Darul Izzah Abai South Solok Tahfidz Qur'an (RTQ) house, ( 3) the relationship between parental attention and the learning outcomes of students at the Darul Izzah Abai South Solok Tahfidz Qur'an (RTQ) house. This research uses a quantitative approach with descriptive correlation research. The population of this study was Darul Izzah students totaling 38 people and 79% were sampled, namely 30 people using cluster random sampling techniques. The data collection technique is a questionnaire. Data analysis techniques use percentage formulas and product moment correlation formulas. The results of the research show that: (1) there is low parental attention, (2) the low learning outcomes of Darul Izzah students seen from the January June 2023 semester exams, (3) there is a significant relationship between parental attention and the learning outcomes of Tahfidz Qur'an home students. (RTQ) Darul Izzah Abai South Solok. It is recommended that: (1) RTQ managers remind parents to pay more attention to their children and support their children's religious education at RTQ; (2) Parents should be able to increase their attention to children's learning activities, both in terms of providing supervision, providing guidance and care. Apart from that, parents should pay attention to their children's education, parents better understand the nature and importance of RTQ in order to fulfill their children's religious education needs; (3) For future researchers to be able to look for other variables related to learning outcomes. Keywords: attention, learning outcomes.